Medicine : PreTest self-assessment and review - Berk, S. L.; Davis, William R.; Urban, Robert S. (New York : McGraw-Hill, 2004)
Completely revised, these reviews for subjects tested on the USMLE Step 2 feature 500 questions, including 200 new in clinical vignette format, with answers and explanations. All questions are reviewed by recent USMLE Step 2 test-takers.
1. Infectious disease -- 2. Rheumatology -- 3. Pulmonary disease -- 4. Cardiology -- 5. Endocrinology and metabolic disease -- 6. Gastroenterology -- 7. Nephrology -- 8. Hematology and oncology -- 9. Neurology -- 10. Dermatology -- 11. General medicine and prevention -- 12. Allergy and immunology -- 13. Geriatrics -- 14. Women's health.
Includes bibliographical references.
Keywords: Examination questions; Examinations; Medicine